External validation of the US and UK kidney donor risk indices for deceased donor kidney transplant survival in the Australian and New Zealand population. Issue 12 (3rd June 2019) - Clayton, Philip A; Dansie, Kathryn; Sypek, Matthew P; White, Sarah; Chadban, Steve; Kanellis, John; Hughes, Peter; Gulyani, Aarti; McDonald, Stephen
Abstract: Background: The US Kidney Donor Risk Index (KDRI) and the UK KDRI were developed to estimate the risk of graft failure following kidney transplantation. Neither score has been validated in the Australian and New Zealand (ANZ) population. Methods: Using data from the Australia and New Zealand Organ Donor (ANZOD) and Dialysis and Transplant (ANZDATA) Registries, we included all adult deceased donor kidney-only transplants performed in ANZ from 2005 to 2016 ( n = 6405). The KDRI was calculated using both the US donor-only and UK formulae. Three Cox models were constructed (Model 1: KDRI only; Model 2: Model 1 + transplant characteristics; Model 3: Model 2 + recipient characteristics) and compared using Harrell's C-statistics for the outcomes of death-censored graft survival and overall graft survival. Results: Both scores were strongly associated with death-censored and overall graft survival (P < 0.0001 in all models). In the KDRI-only models, discrimination of death-censored graft survival was moderately good with C-statistics of 0.63 and 0.59 for the US and UK scores, respectively. Adjusting for transplant characteristics resulted in marginal improvements of the US KDRI to 0.65 and the UK KDRI to 0.63. The addition of recipient characteristics again resulted in marginal improvements of the US KDRI to 0.70 and the UK KDRI to 0.68. Similar trends were seen for the discrimination of overall graft survival. Conclusions: The US and UK KDRI scores were moderately good at discriminating death-censored and overall graft survival in the ANZ population, with the US score performing slightly better in all models.